Knowledge, attitude and practice related to universal precaution among nursing and medical students - Al-Araji, Laith Issa Yassin; Mohd Sariman , Muhammad Hariz; Wan Su, Kamaruzaman (2012)
Introduction: A good practice of universal precaution (UP) is a powerful tool to reduce the risk of contacting nosocomial infections in clinical settings. The knowledge level of UP affects the positive attitude and good practice of universal precaution. Objectives: The aim of the study is to identify knowledge, attitudes and practice related to UP among nursing and medical students of International Islamic University Malaysia (IIUM). This study was done to investigate the relationship of socio-demographic data (age, gender, course taken and clinical experience) towards knowledge, attitude and practice of UP also to determine source of info related to UP. Method: A cross-sectional study was conducted at IIUM Kuantan Campus. Convenience sampling method was used to select the sample. 276 respondents involved in this study and the data was collected using self-administered questionnaire modified from a valid and reliable measure. The data had been analyzed by using PASW Statistics Version 18.0 in terms of descriptive statistics, Spearman Correlation Coefficient, Mann-Whitney U test and Kruskal-Wallis test were carried out for significant test. Results: The result showed that IIUM Nursing and medical students have a good knowledge level, positive attitude and good practice of universal precaution with all three domains scored more than 75% above total population score. Age, gender, course taken and clinical experience certainly have effect towards the knowledge, attitude and practice of UP. Various sources of info noted from respondents. Conclusion: In conclusion, IIUM nursing and medical students have good knowledge, attitude and practice of UP. Age, gender, course taken and clinical experience has their own effect towards knowledge, attitude and practice of UP. Curriculum was the main source of info of UP.